Enhancing Supply Chain Efficiency: Implementation of Vendor Managed Inventory in Inventory Routing Problem - Harahap, Afif Zuhri Muhammad Khodri; Mohd Zahari, Ahmad Suffian; Ali, Noor Malinjasari; Ma’arof, Rabiatul Adawiyah (Information Management and Business Review, 2024)
This article explores the integration of Vendor Managed Inventory (VMI) into the framework of the Inventory Routing Problem (IRP) as a strategic approach to enhance supply chain efficiency. VMI involves suppliers taking an active role in managing customer inventory levels and fostering real-time communication and data sharing. The Inventory Routing Problem addresses the challenge of optimizing delivery routes while simultaneously managing inventory levels. The benefits of implementing VMI in IRP include improved demand forecasting, reduced stockouts and overstock situations, and optimized routing and transportation. The study applies a method that strategically integrates Vendor Managed Inventory (VMI) into the Inventory Routing Problem (IRP) framework, utilizing real-time data sharing and optimized routing algorithms to enhance supply chain efficiency. This approach is evaluated through research findings highlighting its benefits and implementation challenges. Thus, we discuss the potential advantages and challenges associated with this integration. While VMI in IRP offers substantial benefits, data security, cultural shifts, and IT system integration must be addressed for successful implementation. This article provides insights into the promising synergy between VMI and IRP, offering organizations a competitive edge in the dynamic supply chain management landscape.